Orchid (Orchidaceae) Inventory in Isau-Isau Wildlife Conservation Resort Area IX Lawang Agung Village, South Sumatra - Felia Melinda. H; Harmida Harmida; Nita Aminasih (UIN Sunan Gunung Djati Bandung, 2022)
Orchidaceae is one of the plant families which occupies 7-10% of the total flowering plants in the world. Of the 25,000 species of orchids in the world, 6,000 species are found in various forests in Indonesia, including Sumatra. South Sumatra save high diversity of orchid and one of them is in Isau-Isau Wildlife Conservation. This area has various types of plants, including orchids. Diversity orchids in the area have not gotten any attention, so the data regarding orchids in the Isau-Isau Wildlife Conservation, especially in Resort Conservation Area IX Lawang Agung Village, Mulak Ulu District, Lahat Regency, South Sumatra still limited and not well documented, so that need further research to know types of orchids in the area. The research found 22 species, consisting of 21 epiphyte orchids and 1 terrestrial orchid. Many orchids were found in the secondary forest of 16 species. An endemic orchid of South Sumatra was found in this research, it is Vanda foetida. Host plants found were 11 plants, 7 can identify and 4 not can be identified.